Users’ perspectives on Implanon in Malaysia, a multicultural Asian country - Asmah Mastor; Si Lay Khaing; Siti Zawiah Omar (Dove Medical Press, 2011)
Asmah Mastor, Si Lay Khaing, Siti Zawiah Omar Department of Obstetrics and Gynaecology, University of Malaya, Kuala Lumpur, MalaysiaBackground: The primary objective of this study was to evaluate Malaysian women’s ¬perception, acceptance, and views on Implanon® as a contraceptive method. We also aimed to identify women who favor Implanon, their vaginal bleeding patterns, nonmenstrual adverse events, reasons for discontinuation, and effect of Implanon on breastfeeding.Study design: This study followed up 140 women after insertion of Implanon at the University of Malaya Medical Centre by examination of their medical records and telephone interviews. User profile, discontinuation rate, reasons for choice of Implanon, discontinuation, menstrual and nonmenstrual side effects, and satisfaction rate were assessed.Results: The average age of users was 34.7 years, and 94.2% were para 2 and above. The ethnic distribution of the women reflected that of the general Malaysian population. The majority had at least secondary education (94.2%), with 41.2% having a higher degree. All of the users reported that they chose Implanon because it does not need compliance, and 72.1% felt that Implanon was cost-effective in the long term. Most users (70%) reported irregular menses and this was the main reason given for discontinuation. The vast majority reported an overall decrease in menstrual blood loss. Almost half (46%) suffered prolonged bleeding/spotting, and infrequent bleeding was experienced by 71 users (50.7%). Half of the women did not experience any nonmenstrual adverse events. The commonest complaint was weight gain, with the next most common complaints being hair loss, acne, headache, nausea, mood swings, and reduced libido. Most of the nursing mothers denied a reduction in breast milk. There was a high mean satisfaction score with Implanon.Conclusion: Implanon is well accepted by Malaysian women despite a high incidence of irregular bleeding which was found to be a major concern among women who discontinued the implant.Keywords: implanon, contraception, implant, etonogestrel